Exploring simulation design for mental health practice preparation: a pilot study with learners and preceptors - Diane E MacKenzie; Niki Kiepek; Leanne Picketts; Stephanie Zubriski; Karen Landry; Jonathan Harris (Scholarworks @ WMU, 2021)
The purpose of this exploratory pilot study was to determine the feasibility of delivering mental health practice simulations for occupational therapy learners, and whether different debriefing approaches yielded performance differences over successive simulations. Five clinical preceptors and nine first year MScOT students participated in this mixed-method study. In week one simulations, one student group received preceptor facilitated debriefing while the other group used self-debriefing. Both groups used the same scripted questions informed by an advocacy-inquiry approach. In the second week, both groups received the preceptor-led debriefing. Preceptors rated student performances while students self-rated their confidence, competence screen, and satisfaction using standardized tools. Ratings of simulation performance revealed gaps in practice knowledge and the process of practice. Preceptor-led debriefing for both groups resulted in greater depth of reflection and insight into learning gaps and opportunities for continued improvement. The self-debriefing group reported feeling less confident in the simulations. Preceptors reported the scripted advocacy inquiry debriefing approach helped draw out clinical reasoning that could not be observed from performance alone. Simulation may be an effective teaching tool for developing core practice competencies. Design and debriefing styles appear to impact preceptor feedback and the depth of learner critical reflection. Further study is required for generalization.